SISTEM INFORMASI EVALUASI PENJUALAN BERBASIS WEBSITE PADA PT LASBON TECHNOLOGY INDONESIA - Sari, Hanifa Rosyida; Widodo, Arifin Puji; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
PT Lasbon Technology Indonesia, which is engaged in selling women's products such as clothes, pants, skirts, bags, watches, wallets, and mukenah does not yet have a Sales Evaluation Information System. From the results of the interview, it was found several problems such as the company so far only produced information limited to sales recapitulations obtained from copies of sales notes. The results of the recording have not been able to produce sufficient information for managers in evaluating sales in each branch. Because the information that can be obtained is limited to information on the number of items sold each period. Not being able to know which items are selling best, or information on turnover of items that have the highest sales speed. If the information generated is more detailed, it will help managers in making sales target decisions. And so far, the company also does not have a procedure to set and monitor the achievement of sales targets. This makes it difficult for PT Lasbon Technology Indonesia to be motivated to make sales achievements because the information generated is not satisfactory. The solution to solve this problem is to create a Website-Based Sales Evaluation Information System at PT Lasbon Technology Indonesia, which is able to produce sales information, sales turnover information, inventory information, and sales target information. Second, being able to determine sales targets by using the sell-through method which is used to calculate the percentage of sales speed of each item and using the top down method as a parameter to determine the sales target of the manager. Based on the results of blackbox testing and evaluation of excel calculations with the calculation of the sales evaluation information system that has been carried out, it shows that the Website-Based Sales Evaluation Information System at PT Lasbon Technology Indonesia can carry out the sales process validly, can perform the sales turnover calculation process using the sell-through method with valid, and the calculation process of determining sales targets using the top down method with valid. So that it can make it easier for managers to monitor sales and monitor sales targets in each branch.